PERSEPSI PETANI TENTANG KARAKTERISTIK INOVASI SISTEM TANAM JAJAR LEGOWO PADI SAWAH (Oryza sativa L) - Astuti, Yulianti (Jurnal Ilmu-Ilmu Pertanian, 2019)
This study aims to determine farmers perception about the characteristics of innovations that include relative advantage, compatibility, complexity, tribality and observability Jajar Legowo planting system. The study was conducted from February to July 2019 in Selomartani village, Kalasan District, Sleman Regency DIY. Methods of study are quantitative descriptive. Farmers sample were determined by proportional random sampling. The results of the study showed that farmers perception of the Jajar Legowo planting system is beneit, appropriate, uncomplicated, fairly easy to try and easy observed. Needs to be done counselling planting row creation because this component not in accordance with the customs of farmers. The design of the empowerment was done by manufacture rice planting equipment for planting Jajar Legowo namely caplak as a tool to build the planting line. Thereby will increase the perception of farmers to Jajar Legowo planting system.